Regional Fluid-Attenuated Inversion Recovery (FLAIR) at 7 Tesla correlates with amyloid beta in hippocampus and brainstem of cognitively normal elderly subjects - Schreiner, Simon J.; Liu, Xinyang; Gietl, Anton F.; Wyss, Michael; Steininger, Stefanie C.; Gruber, Esmeralda; Treyer, Valerie; Meier, Irene B.; Kälin, Andrea M.; Leh, Sandra E.; Buck, Alfred; Nitsch, Roger M.; et al. (Frontiers in Aging Neuroscience, 2014)
Background: Accumulation of amyloid beta (Aβ) may occur during healthy aging and is a risk factor for Alzheimer Disease (AD). While individual Aβ-accumulation can be measured non-invasively using Pittsburgh compound-B positron-emission-tomography (PiB-PET), Fluid-Attenuated Inversion Recovery (FLAIR) is a Magnetic Resonance Imaging (MRI) sequence, capable of indicating heterogeneous age-related brain pathologies associated with tissue-edema. In the current study cognitively normal elderly subjects were investigated for regional correlation of PiB- and FLAIR- intensity. Methods: 14 healthy elderly subjects without known history of cognitive impairment received 11C-PiB-PET for estimation of regional Aβ-load. In addition, whole brain T1-MPRAGE and FLAIR-MRI sequences were acquired at high field strength of 7 Tesla (7T). Volume-normalized intensities of brain regions were assessed by applying an automated subcortical segmentation algorithm for spatial definition of brain structures. Statistical dependence between FLAIR- and PiB-PET intensities was tested using Spearman's rank correlation coefficient (rho), followed by Holm-Bonferroni correction for multiple testing. Results: Neuropsychological testing revealed normal cognitive performance levels in all participants. Mean regional PiB-PET and FLAIR intensities were normally distributed and independent. Significant correlation between volume-normalized PiB-PET signals and FLAIR intensities resulted for Hippocampus (right:rho=0.86; left:rho=0.84), Brainstem (rho=0.85) and left Basal Ganglia vessel region (rho=0.82). Conclusions: Our finding of a significant relationship between PiB- and FLAIR-intensity mainly observable in the Hippocampus and Brainstem, indicates regional Aβ associated tissue-edema in cognitively normal elderly subjects. Further studies including clinical populations are necessary to clarify the relevance of our findings for estimating individual risk for age-related neurodegenerative processes such as AD.